Global Risk Factors and Macroeconomic Conditions Affect Jakarta Islamic Index (JII): Evidence from Indonesia - Husnah, Siti Syavinatul; Nugraha, Deni Pandu; Rizal, Sofyan (Maliki Islamic Economics Journal, 2022)
This study aims to analyze three things, namely analyzing the causality relationship between variables. Analyze the short-term relationship between macroeconomic variables with JII Stock Price and Trade Volume and analyze the long-term relationship between macroeconomic variables with JII Stock Price and Trade Volume. The sample used is the JII30 Index and the trading volume from JII 30 from 2008-2020. The results of this study indicate three things, firstly it is found that several variables have a causal relationship in either one or two directions, then from testing the short-term effect it is found that only the oil price variable has a significant effect on JII while other variables do not, while the short-term effect test It was found that all macroeconomic variables had no significant effect on volume. Finally, from the long-term test results, only the Inflation variable has no significant effect on the JII variable in the long term, while only the BI Rate and Inflation variables have no significant effect on trading volume.